Kapasitas Sumber Daya Manusia, Pengendalian Internal dan Pemahaman Sistem Akuntansi terhadap Kualitas Laporan Keuangan Desa - Kautsar, Nabila Al; Widaryanti, Widaryanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
The quality of village financial management is very important. This requires the village government to manage village finances professionally, effectively, efficiently and responsibly. The aim of this research is to determine the quality of village government financial reporting in order to achieve good quality financial management at the village level, therefore research was conducted regarding the impact of human resource capabilities, internal control and understanding of the accounting system on villages. The object of this research is the village government in Karangrayung District. The sampling technique in this research is a saturated sampling technique (census). The data collection tool in this research is a questionnaire. Research data uses primary data, directly through questionnaires, and is analyzed using SPSS version 26. Data is analyzed using multiple linear regression analysis to test the hypothesis. The findings show that human resource capabilities influence the quality of village level financial reporting. Internal control influences the quality of village financial reporting. Understanding the accounting system influences the quality of village level financial reporting. Keywords: Presentation of Human Resource Capacity, Internal Control, Understanding of Accounting Systems, Quality of Village Financial Reports.